On a conjecture of Erd\H{o}s on additive basis of large orders : On a conjecture of Erd\H{o}s - Agama, Theophilus (My University, 2022)
Using the methods of multivariate circles of partition, we prove that for any additive base A of order h ≥ 2 the upper bound. #Check uploaded file for detailed abstract
Keywords: circle of partition; axes; generalized circles of partition; generalized density